Actualization of Uswatun Hasanah as a Framework for Islamic Moderation Against Religious Politicization in Indonesia - Wardah Dede Aenul; Kris Nandang (UIN Siber Syekh Nurjati Cirebon, 2024)
The phenomenon of religious politicization, which entails the exploitation of religion for political gain, poses a serious threat to national unity by fostering divisions among religious communities and undermining democratic principles. This practice stands in stark contrast to the values of religious moderation, which emphasize justice, tolerance, and harmony. Through an exploration of Islamic moderation, this study highlights the concept of uswatun hasanah (a virtuous role model) as a strategic framework to mitigate the negative impacts of religious politicization. Employing a qualitative research approach focused on library research, the study conducts a thematic analysis of Qur'anic verses using descriptive-analytic methods. The findings reveal that religious politicization not only disrupts societal cohesion but also underscores the urgent need for religious moderation as a means to counteract the misuse of religion for political purposes. By advocating the emulation of positive role models, Islam provides a pathway to cultivate virtuous behavior and promote harmony. Furthermore, the concept of uswatun hasanah can be actualized both in society and the digital realm through the creation and dissemination of moderate content while actively filtering out hoaxes, misinformation, and divisive materials. These efforts highlight the pivotal role of uswatun hasanah in fostering interfaith harmony and protecting societal unity from the divisive effects of religious politicization.